Bipolar membrane containing hydroxyl MOF (Metal Organic Framework) catalyst middle layer as well as preparation method and application of bipolar membrane

By using the intermediate layer of hydroxy MOF catalyst in the bipolar membrane, combining anion and cation exchange resins and binders, the problems of high hydrolysis voltage and poor stability of the bipolar membrane are solved, and high performance and low cost dual-cost Electrode film preparation, suitable for photo/electrochemical hydrolysis, fuel cells and electrochemical ammonia synthesis.

CN119175007AActive Publication Date: 2024-12-24ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202411309006.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-24
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The existing bipolar membranes have problems such as high hydrolysis voltage, slow hydrolysis rate, poor membrane structure stability and high production costs, which limit their widespread use in industrial applications.

Method used

Using an intermediate layer bipolar film containing hydroxyl MOF catalyst, an anion exchange resin and a cation exchange resin are added as exchange groups, and a binder and MOF material containing hydroxyl groups are prepared by casting method. heterogeneous bipolar membrane.

Benefits of technology

The performance improvement and stability enhancement of the bipolar membrane are achieved, the hydrolysis voltage is reduced, the hydrolysis rate and mechanical properties are improved, the service life of the membrane is extended, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119175007A_ABST
    Figure CN119175007A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of bipolar membranes, and particularly relates to a bipolar membrane containing a hydroxyl MOF catalyst middle layer and a preparation method and application of the bipolar membrane. The high-performance and high-stability heterogeneous bipolar membrane is prepared by taking anion and cation exchange resin as an exchange group of the bipolar membrane, adding an adhesive and taking an MOF material containing a hydroxyl group as a water dissociation catalyst. The raw materials are low in cost and wide in source and have excellent ion exchange capacity, and the prepared bipolar membrane is better in performance and simple in manufacturing process. The hydroxyl MOF water dissociation catalyst simultaneously contains a hydroxyl group and a metal group, so that the specific surface area of the catalyst can be effectively prolonged, transfer of protons from water molecules to fixed charge groups is enhanced, and water dissociation in a bipolar membrane is accelerated. By adding the adhesive and the carbon-containing woven fabric fibers, the stability of the membrane structure is enhanced, the service life of the membrane is prolonged, and the mechanical property and the conductivity of the bipolar membrane are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bipolar membranes, and in particular relates to a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer and a preparation method and application thereof. Background Art

[0002] The bipolar membrane is a layered ion exchange membrane with a special structure. It consists of two layers of polymer layers with fixed opposite charges. One layer only allows anions to pass through (anion exchange membrane layer), while the other layer only allows cations to pass through (cation exchange membrane layer). When a positive bias is applied to both sides of the bipolar membrane, the H + and OH - Driven by the electric field, they migrate to the interface layer to compound into water molecules; when a reverse bias is applied to both sides of the bipolar membrane, the positive and negative ions in the middle layer migrate to the main solution through the anion and cation membrane layers respectively under the drive of the electric field, thereby forcing the water molecules in the middle layer to dissociate. + and OH - Driven by the potential difference between the cathode and anode, the water migrates to the main solution on both sides of the membrane. At the same time, the consumed water diffuses from the main solution through the membrane layer to the middle layer for replenishment. Compared with conventional water dissociation, this process has the advantages of no gas generation and low energy consumption.

[0003] Bipolar membranes can effectively prevent ions from crossing on both sides of the membrane layer, providing different reaction environments on both sides and broadening its application range. Currently, most bipolar membranes are limited by problems such as high water dissociation voltage, membrane shedding, and catalyst leakage, and cannot be applied on a large scale.

[0004] In order to meet the industrial application requirements of bipolar membranes in different fields, the performance of bipolar membranes must be continuously improved, and precise regulation of the bipolar membrane interface layer is an important means to improve its performance. The regulation of the water dissociation voltage of the bipolar membrane is mainly achieved by changing the type of catalyst and the preparation process, while problems such as membrane shedding are mainly improved through the composite process of the membrane layer. At the same time, in addition to regulating the materials of the anion and cation membrane layers, the stability and fixing method of the interface layer catalyst also have a huge impact on the stability of the bipolar membrane.

[0005] Since the current bipolar membrane is mainly used in the bipolar membrane electrodialysis process, the present invention introduces a method for preparing a bipolar membrane with excellent performance and stability and a variety of effective catalysts, providing a new idea for preparing a bipolar membrane with excellent performance and stability. Summary of the invention

[0006] The present invention aims to overcome the defects of the bipolar membranes in the prior art, such as high water dissociation voltage, slow water dissociation rate, poor membrane structure stability and high production cost, and provides a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer and a preparation method thereof, and applies the bipolar membrane to photo / electrochemical water splitting hydrogen production process, fuel cells, electrochemical ammonia synthesis process and bipolar membrane electrodialysis.

[0007] To achieve the above-mentioned purpose, the present invention is implemented by the following technical solutions: A method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer comprises the following steps: (S.1) Preparation of hydroxyl MOF water dissociation catalysts: Weighing hydrated metal chloride and dissolving it in N,N-dimethylformamide solution, adding 2-hydroxyterephthalic acid, stirring evenly and sealing it in a reaction kettle, cooling it naturally after the heating reaction is completed, taking the product and centrifuging, washing and drying it to obtain a hydroxyl MOF hydrolysis catalyst M-MOF-OH; (S.2) Preparation of bipolar membrane: Add anion exchange resin powder and cation exchange resin powder to the binder solution respectively, stir evenly, and obtain anion membrane casting solution and cation membrane casting solution respectively; fix the woven fabric on a clean glass plate and cast the anion membrane casting solution thereon and dry it, and obtain the anion exchange membrane layer after it is completely dried; An ethanol solution containing a hydroxyl MOF water dissociation catalyst M-MOF-OH is dripped onto the anion exchange membrane layer and dried to obtain an intermediate layer after complete drying; A cationic membrane casting solution is coated on the intermediate layer and dried, thereby forming a cation exchange membrane layer on the intermediate layer, and finally obtaining a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer.

[0008] The present invention utilizes anion exchange resin and cation exchange resin as the exchange groups of the bipolar membrane, and by adding an adhesive and using a MOF material containing a hydroxyl group as a water dissociation catalyst, a high-performance, high-stability heterogeneous bipolar membrane is produced by a tape casting method. Specifically, the present invention uses anion exchange resin and cation exchange resin as raw materials, which are low-cost, widely available, and easy to obtain. At the same time, the hydroxyl MOF water dissociation catalyst of the present invention contains hydroxyl groups and metal groups at the same time. The catalytic effect of the hydroxyl group and the porous structure of the MOF material itself have strong adsorption and can effectively extend the specific surface area of ​​the catalyst. In addition, the metal group also has excellent hydration ability, and acts as an active surface site (M-OH) in the ion exchange membrane matrix, which helps to enhance the transfer of protons from water molecules to fixed charge groups, thereby accelerating water dissociation in the bipolar membrane.

[0009] In addition, the ion exchange resin selected by the present invention has excellent ion exchange capacity, and the obtained bipolar membrane has better performance and simple manufacturing process. In addition, at the physical level, the stability of the membrane structure is enhanced by adding an adhesive, which helps to extend the service life of the membrane. The present invention also significantly improves the mechanical properties and conductivity of the bipolar membrane by adding carbon-containing woven fabric fibers, thereby ensuring the stability of the bipolar membrane.

[0010] On the other hand, multi-metal MOF materials show higher catalytic activity due to their compact structure, good stability and high electron transfer efficiency. The present invention also uses the combination of two different metal cations to effectively enhance conductivity and promote the rapid oxidation reaction between different metal sites in the MOF structure, thereby improving catalytic efficiency. This controllable integration of functional components helps to construct multifunctional complexes with advanced properties and effectively enhance the activity of catalytic reactions and other reactions.

[0011] The bipolar membrane containing the hydroxyl MOF catalyst intermediate layer prepared by the method of the present invention has a high conductivity at 100 mA / cm 2 The transmembrane voltage under the current density is only 1.29V. The present invention selects different metal ions and MOF materials containing hydroxyl groups to prepare different bipolar membranes containing hydroxyl MOF catalyst intermediate layers. The hydrolysis voltage is reduced to varying degrees. Among the different catalysts prepared, Ni-MOF-OH has the best catalytic effect. According to data analysis, the catalyst loading is best at about 0.1g / L. In the stability test of the bipolar membrane, at 100mA / cm 2 After 10 hours at the current density, the transmembrane voltage of the bipolar membrane containing the hydroxyl MOF catalyst intermediate layer of the present invention only increases by 6%, and has excellent stability.

[0012] Preferably, the metal ion contained in the hydrated metal chloride in step (S.1) is Al 3+ Mg 2+ Sn 2+ , any one or more combinations of transition metal ions.

[0013] As a further preference, the transition metal ion is Co 2+ 、Ni 2+ Cr 3+ , Fe 3+ , Fe 2+ 、Ru 3+ 、V 3+ 、V 5+ , Mn 2 + , Mn 4+ , Ir 3+ , Pt 2+ , Pt4+ 、Eu 3+ 、Ti 2+ , Pd 2+ 、Ag + 、Mo 2+ Any one of .

[0014] Preferably, the molar ratio of the metal ion contained in the hydrated metal chloride in step (S.1) to the 2-hydroxyterephthalic acid is 0.1-1:0.5-1.

[0015] Preferably, the amount of N,N-dimethylformamide solution added in step (S.1) is 30-60 mL.

[0016] Preferably, in step (S.1), the stirring reaction time is 30-100 min; the reaction temperature of the heating reaction is 120-180° C., and the reaction time of the heating reaction is 10-18 h.

[0017] Preferably, the cation exchange groups contained in the cation exchange resin powder in step (S.2) are any one or more of sulfonic acid groups, carboxyl groups, phosphonic acid groups, phosphinic acid groups, arsenic acid groups and selenic acid groups; The anion exchange groups contained in the anion exchange resin powder are any one or more combinations of quaternary ammonium salts, primary amines, secondary amines, tertiary amines, and tertiary sulfonium groups; The binder contained in the binder solution is any one or more combinations of polyacrylonitrile, polyethylene, polyvinyl chloride, polyvinyl alcohol, fluororubber, styrene-butadiene rubber, cellulose derivatives, polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinylidene fluoride, polysulfone, polyetheretherketone, styrene-ethylene-butylene-styrene, and polyphenylene ether.

[0018] Preferably, the concentration of the binder solution in step (S.2) is 2-15%; The mass ratio of the anion and cation exchange resin powder contained in the anion and cation membrane casting solution to the binder contained in the binder solution is 0.2~1.5:1; The concentration of anion membrane casting solution and cationic membrane casting solution is 5~20%; The concentration of the ethanol solution containing the hydroxyl-based MOF water dissociation catalyst M-MOF-OH is 0.05~0.2g / L.

[0019] Preferably, the drying temperature in step (S.2) is 50-60°C.

[0020] The bipolar membrane containing a hydroxyl MOF catalyst intermediate layer prepared by the preparation method as described above comprises, in sequence, an anion exchange membrane layer, an intermediate layer having a water dissociation catalytic effect, and a cation exchange membrane layer, and is characterized in that the intermediate layer comprises a MOF catalyst containing a hydroxyl group.

[0021] The method for preparing the bipolar membrane containing the hydroxyl MOF catalyst intermediate layer as described above is applied in the fields of photo / electrochemical hydrolysis hydrogen production process, fuel cell, electrochemical ammonia synthesis process, and bipolar membrane electrodialysis.

[0022] Therefore, the present invention has the following beneficial effects: (1) The present invention uses anion exchange resin and cation exchange resin as the exchange groups of the bipolar membrane, adds a binder and uses a MOF material containing a hydroxyl group as a water dissociation catalyst to produce a high-performance, high-stability heterogeneous bipolar membrane by a casting method. The raw materials are low-cost and widely available, have excellent ion exchange capacity, and the obtained bipolar membrane has better performance and a simple manufacturing process; (2) The hydroxyl MOF water dissociation catalyst of the present invention contains both hydroxyl groups and metal groups. The catalytic effect of hydroxyl groups and the porous structure of the MOF material itself have strong adsorption properties and can effectively extend the specific surface area of ​​the catalyst. In addition, the metal group also has excellent hydration ability and acts as an active surface site (M-OH) in the ion exchange membrane matrix, which helps to enhance the transfer of protons from water molecules to fixed charge groups, thereby accelerating water dissociation in the bipolar membrane; (3) The present invention enhances the stability of the membrane structure by adding an adhesive, which helps to extend the service life of the membrane. The mechanical properties and conductivity of the bipolar membrane are significantly improved by adding carbon-containing woven fabric fibers, thereby ensuring the stability of the bipolar membrane; (4) The present invention utilizes the combination of two or more different metal cations to effectively enhance the conductivity and promote the rapid oxidation reaction between different metal sites in the MOF structure, thereby effectively enhancing the reaction activity and improving the catalytic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A preparation route for hydroxyl-based MOF water dissociation catalysts.

[0024] Figure 2 Roadmap for the preparation of bipolar membranes containing hydroxyl MOF catalyst interlayers.

[0025] Figure 3 The scanning electron microscope images of the hydroxyl MOF water dissociation catalyst and the cross-sectional scanning electron microscope images of the bipolar membrane containing the hydroxyl MOF catalyst intermediate layer are compared with the cross-sectional scanning electron microscope images of the blank bipolar membrane.

[0026] Figure 4 This is the test result of the bipolar membrane current-voltage curve under different metal group conditions.

[0027] Figure 5The graph shows the test results of the bipolar membrane current-voltage curve under different concentrations of hydroxyl MOF water dissociation catalyst conditions.

[0028] Figure 6 The bipolar membrane containing a hydroxyl MOF catalyst intermediate layer is 100mA / cm 2 Cyclic stability curves at current density of .

[0029] Figure 7 This is a graph showing the test results of different bipolar membrane current-voltage curves. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments of the specification. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0031] Example 1 This embodiment provides a method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer.

[0032] A method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer comprises the following steps: (S.1) Preparation of hydroxyl MOF water dissociation catalyst (Ni-MOF-OH): Weigh 0.2377 g (0.001 mol) of NiCl2•6H2O and dissolve it in 40 mL of N,N-dimethylformamide (DMF) solution, and add 1.811 g of 2-hydroxyterephthalic acid to keep the metal ion Ni in the whole system. 2+ The molar ratio of 2-hydroxyterephthalic acid to 2-hydroxyterephthalic acid is 1:1. After stirring for 60 minutes, it is packaged in a polytetrafluoroethylene reactor and heated at 150°C for 12 hours. After the reaction is completed, it is naturally cooled, the product is centrifuged, washed three times with anhydrous ethanol, and finally vacuum dried at 80°C for 24 hours to obtain a hydroxyl MOF hydrolysis catalyst (Ni-MOF-OH). The preparation route of the hydroxyl MOF hydrolysis catalyst is as follows Figure 1 As shown; (S.2) Preparation of bipolar membrane: The purchased anion and cation exchange resin particles were crushed to a diameter of less than 10 μm using a ball mill (QM-3SP2 planetary ball mill of Nanjing Nanda Instrument Co., Ltd.) to obtain anion and cation exchange resin powders. Then, the anion and cation exchange resin powders were added to a polyacrylonitrile solution with a concentration of 8%, stirred for more than 12 hours to ensure that the anion and cation exchange resin particles were evenly dispersed, and an anion membrane casting solution with a concentration of 10% and a cationic membrane casting solution with a concentration of 10% were obtained respectively. Among them, the mass ratio of anion and cation exchange resin powders contained in the anion and cation membrane casting solution to polyacrylonitrile contained in the polyacrylonitrile solution was 1.2:1. The carbon-containing woven fabric fiber was fixed on a clean glass plate with tape, and the anion membrane casting solution was poured on it, and then scraped with a scraper to a thickness of 200 μm, and the anion exchange membrane layer was obtained after complete drying. The thickness of the anion exchange membrane layer formed after drying is 70~120 μm, and the final thickness of the anion exchange membrane layer depends on the concentration of the anion membrane casting solution. After the anion exchange membrane layer is completely dried, 2 1 mL of 0.1 g / L ethanol solution containing a hydroxyl MOF hydrolysis catalyst (Ni-MOF-OH) is dripped onto the anion exchange membrane layer, and the intermediate layer is obtained after complete drying. The cationic membrane casting liquid is then poured on the intermediate layer and dried completely to form a cation exchange membrane layer on the upper surface of the intermediate layer. The thickness of the cation exchange membrane layer is controlled to be similar to that of the anion exchange membrane layer, and the drying temperature is maintained at 60°C. Finally, a bipolar membrane containing an intermediate layer of a hydroxyl MOF catalyst is obtained. The bipolar membrane containing an intermediate layer of a hydroxyl MOF catalyst is immersed in a 0.1~0.5 mol / L sodium chloride solution for more than 2 hours for testing. The preparation route of the bipolar membrane containing an intermediate layer of a hydroxyl MOF catalyst is as follows: Figure 2 shown.

[0033] Example 2 The difference between this embodiment and embodiment 1 is that: This embodiment provides a method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer, wherein in step (S.1), 0.2703 g (0.001 mol) of FeCl3•6H2O is used to replace 0.2377 g (0.001 mol) of NiCl2•6H2O. In the final step (S.1), a hydroxyl MOF water dissociation catalyst (Fe-MOF-OH) is obtained. In step (S.2), a 12.56 cm 2 1 mL of 0.1 g / L ethanol solution containing a hydroxyl MOF hydrolysis catalyst (Fe-MOF-OH) was dripped onto the anion exchange membrane layer. Others were the same as in Example 1.

[0034] Example 3 The difference between this embodiment and embodiment 1 is that: In this embodiment, a method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer is provided, wherein in step (S.1), 0.1188 g (0.0005 mol) of NiCl2•6H2O and 0.1352 g (0.0005 mol) of FeCl3•6H2O are used to replace 0.2377 g (0.001 mol) of NiCl2•6H2O. Finally, in step (S.1), a hydroxyl MOF water dissociation catalyst (Ni / Fe-MOF-OH) is obtained. In step (S.2), a 12.56 cm 2 1 mL of 0.1 g / L ethanol solution containing a hydroxyl MOF hydrolysis catalyst (Ni / Fe-MOF-OH) was dripped onto the anion exchange membrane layer. Others were the same as in Example 1.

[0035] Example 4 The difference between this embodiment and embodiment 1 is that: This embodiment provides a method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer, wherein in step (S.1), 0.2664 g (0.001 mol) of CrCl3•6H2O is used to replace 0.2377 g (0.001 mol) of NiCl2•6H2O. In the final step (S.1), a hydroxyl MOF water dissociation catalyst (Cr-MOF-OH) is obtained. In step (S.2), a 12.56 cm 2 1 mL of 0.1 g / L ethanol solution containing a hydroxyl MOF hydrolysis catalyst (Cr-MOF-OH) was dripped onto the anion exchange membrane layer. Others were the same as in Example 1.

[0036] Example 5 The difference between this embodiment and embodiment 1 is that: This embodiment provides a method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer, wherein in step (S.1), 0.2379 g (0.001 mol) of CoCl2•6H2O is weighed and dissolved in 30 mL of DMF solution, and 1.8213 g of 2-hydroxyterephthalic acid is added to keep the metal ions (Co 2+) and 2-hydroxyterephthalic acid in a molar ratio of 0.1:1; stirring reaction time is 30min; heating reaction at 120°C for 10h; obtaining hydroxyl MOF hydrolysis catalyst (Co-MOF-OH). In step (S.2), anion and cation exchange resin powders are added to a polyethylene solution with a concentration of 2% to obtain an anion membrane casting solution with a concentration of 5% and a cationic membrane casting solution with a concentration of 5%, respectively; wherein the mass ratio of anion and cation exchange resin powders contained in the anion and cation membrane casting solution to the polyethylene contained in the polyethylene solution is 0.2:1; the drying temperature is maintained at 50°C. Others are the same as in Example 1.

[0037] Example 6 The difference between this embodiment and embodiment 1 is that: This embodiment provides a method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer, wherein in step (S.1), 0.2033 g (0.001 mol) of MgCl2•6H2O is weighed and dissolved in 60 mL of DMF solution, and 0.0911 g of 2-hydroxyterephthalic acid is added to keep the metal ions (Mg 2+ ) and 2-hydroxyterephthalic acid in a molar ratio of 2:1; stirring reaction time is 100min; heating reaction at 180°C for 18h; obtaining hydroxyl MOF hydrolysis catalyst (Mg-MOF-OH). In step (S.2), anion and cation exchange resin powders are added to a 15% polyvinylidene fluoride solution to obtain anion membrane casting liquid with a concentration of 20% and cationic membrane casting liquid with a concentration of 20%, respectively; wherein the mass ratio of anion and cation exchange resin powders contained in the anion and cation membrane casting liquid to the polyvinylidene fluoride contained in the polyvinylidene fluoride solution is 1.5:1; the drying temperature is maintained at 55°C. Others are the same as in Example 1.

[0038] Comparative Example 1 The difference between this comparative example and Example 1 is: This comparative example provides a method for preparing a blank bipolar membrane, wherein in step (S.2), a blank bipolar membrane having an area of ​​12.56 cm 2 1 mL of ethanol was added to the anion exchange membrane layer to replace 1 mL of 0.1 g / L ethanol solution containing a hydroxyl MOF hydrolysis catalyst (Ni-MOF-OH). Finally, a blank bipolar membrane without a hydroxyl MOF catalyst intermediate layer was obtained. Others were the same as in Example 1.

[0039] Comparative Example 2 The difference between this comparative example and Example 1 is: This comparative example provides a method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer, wherein in step (S.2), the area of ​​the bipolar membrane is 12.56 cm 2 1 mL of 0.05 g / L ethanol solution containing a hydroxyl MOF water dissociation catalyst (Ni-MOF-OH) was dripped onto the anion exchange membrane layer. Others were the same as in Example 1.

[0040] Comparative Example 3 The difference between this comparative example and Example 1 is: This comparative example provides a method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer, wherein in step (S.2), the area of ​​the bipolar membrane is 12.56 cm 2 1 mL of 0.2 g / L ethanol solution containing a hydroxyl MOF water dissociation catalyst (Ni-MOF-OH) was dripped onto the anion exchange membrane layer. Others were the same as in Example 1.

[0041] Comparative Example 4 The difference between this comparative example and Example 1 is: This comparative example provides a method for preparing a bipolar membrane containing a MOF catalyst intermediate layer, wherein the preparation process of the MOF water dissociation catalyst (Ni-NH2-MOF) in step (S.1) is as follows: 2.377 g of NiCl2•6H2O was weighed and dissolved in 45 mL of a mixed solvent (which was prepared by mixing N,N-dimethylformamide, ethanol, and deionized water in a volume ratio of 10:1:5), and 1.811 g of 2-aminoterephthalic acid was added to keep the metal ion Ni in the whole system 2+ The molar ratio of the substance of 2-aminoterephthalic acid is 1:1. After stirring for 60 minutes, it is packaged in a polytetrafluoroethylene reactor and heated at 180°C for 8 hours. After the reaction is completed, it is cooled naturally, and the product is centrifuged and washed three times with DMF respectively, and finally vacuum dried at 80°C for 24 hours to obtain a MOF water dissociation catalyst (Ni-NH2-MOF). In step (S.2), the mass ratio of the anion and cation exchange resin powder contained in the anion and cation membrane casting liquid to the polyacrylonitrile contained in the polyacrylonitrile solution is 1.5:1; the thickness of the anion exchange membrane layer formed after drying is 70~200μm, and the most preferred thickness of the anion exchange membrane layer is 150μm; in an area of ​​12.56cm 2 1 mL of an aqueous solution containing a MOF water dissociation catalyst (Ni-NH2-MOF) with a concentration of 0.1 g / L was dripped onto the anion exchange membrane layer; the drying temperature was maintained at 50° C. Others were the same as in Example 1.

[0042]

Performance testing and analysis

[0043] from Figure 3 It can be seen from the analysis that the cross-sectional image of the bipolar membrane containing the hydroxyl MOF catalyst intermediate layer prepared in Example 1 shows that there is a clear interface between the anion exchange membrane layer and the cation exchange membrane layer, and the intermediate layer and the two ion exchange membrane layers are mutually non-penetrating. Each monopolar membrane layer of the bipolar membrane is obtained by dispersing anion and cation exchange resin powders in a binder solution and layer by layer. The presence of anion and cation exchange resins in the membrane layer increases the surface roughness of the bipolar membrane and increases the reaction area where water dissociation occurs.

[0044] Bipolar membrane current-voltage curve test (IV): The current-voltage curve test device uses a four-chamber electrodialysis device, which consists of a cathode chamber, a cation chamber, an acid chamber, an alkali chamber, and a cathode and an anode. The test system is composed of a voltage-stabilized and current-stabilized power supply, a peristaltic pump, a multimeter, and a reference electrode. During the test, a 1.0 mol / L sodium chloride solution is circulated in the acid chamber and the alkali chamber, and a 1.0 mol / L sodium sulfate solution is circulated in the cathode chamber and the cation chamber. The test current density is 0 mA / cm 2 -200mA / cm 2 .

[0045] Different hydroxyl MOF water dissociation catalysts and their corresponding bipolar membranes containing a hydroxyl MOF catalyst intermediate layer and blank bipolar membranes without a hydroxyl MOF catalyst intermediate layer were prepared according to the methods in Examples 1 to 3 and Comparative Example 1, and current-voltage curve tests (IV) were performed on them respectively. The test results are shown in FIG. Figures 4 and 5 The test results of the bipolar membrane current-voltage curve under different metal group conditions are shown in Figure 4 The test results of the bipolar membrane current-voltage curve under different concentrations of hydroxyl MOF water dissociation catalyst are shown in Figure 5 shown.

[0046] from Figures 4 and 5From the data analysis, it can be seen that the voltage of the bipolar membrane (Examples 1 to 3) with the addition of a hydroxyl MOF water dissociation catalyst is significantly lower than that of the blank bipolar membrane (Comparative Example 1) without the addition of a catalyst. This shows that the introduction of a hydroxyl MOF water dissociation catalyst is beneficial to the dissociation of water in the bipolar membrane. As expected, MOF catalysts containing hydroxyl groups (-OH) and metal groups can accelerate the dissociation of water in the bipolar membrane. At the same time, it was also found that the current-voltage curve of the bipolar membrane is closely related to the loading concentration of the catalyst. As the amount of hydroxyl MOF water dissociation catalyst added increases, the voltage drop first decreases and then increases. This shows that when a hydroxyl MOF material is used as an interfacial layer catalyst for a bipolar membrane, there is an optimal loading concentration. It is difficult to achieve the best catalytic effect at concentrations higher or lower than this optimal level.

[0047] Bipolar membrane stability test: A bipolar membrane containing a hydroxyl MOF catalyst intermediate layer was prepared according to the preparation method in Example 1 and the change of the transmembrane voltage of the bipolar membrane over time under constant current was monitored. The test device was the same as the current-voltage curve test device. The current was set to 100 mA / cm 2 The test voltage interval is 30 minutes, and the total test time is set to 10 hours. The bipolar membrane containing the hydroxyl MOF catalyst intermediate layer is at 100mA / cm 2 The cyclic stability curve at the current density is as follows Figure 6 shown.

[0048] from Figure 6 Data analysis shows that during the 10-hour constant current density test, the transmembrane voltage of the prepared bipolar membrane containing a hydroxyl MOF catalyst intermediate layer increased from 1.29V to 1.36V, and the transmembrane voltage increase rate was only 6%, which indicates that the bipolar membrane containing a hydroxyl MOF catalyst intermediate layer has excellent stability in long-term operation. This also further confirms that the coordination effect and special structure of the hydroxyl MOF water dissociation catalyst in the bipolar membrane containing a hydroxyl MOF catalyst intermediate layer not only effectively improves the water dissociation efficiency, but also significantly enhances the stability of the bipolar membrane.

[0049] A hydroxyl MOF water dissociation catalyst and a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer, a blank bipolar membrane without a hydroxyl MOF catalyst intermediate layer, a MOF water dissociation catalyst (Ni-NH2-MOF) and a bipolar membrane containing a MOF catalyst intermediate layer were prepared according to the methods in Example 1, Comparative Example 1 and Comparative Example 4, and current-voltage curve tests (IV) were performed on them respectively. The test results are as follows: Figure 7 shown.

[0050] from Figure 7From the data analysis, it can be seen that under the same other conditions, the water dissociation voltage of the bipolar membrane containing a MOF catalyst interlayer (the interlayer contains a MOF water dissociation catalyst Ni-NH2-MOF, comparative example 4) and the bipolar membrane containing a hydroxyl MOF catalyst interlayer (the interlayer contains a hydroxyl MOF water dissociation catalyst Ni-MOF-OH, example 1) has a significant difference. The reaction mechanism of amino group (-NH2) mainly involves the basic properties of amino group. The basic properties of amino group come from the isolated electron pairs on its nitrogen atom, which can accept protons or free hydrogen ions (H + ), combines with a proton or free hydrogen ion to form the positively charged conjugate acid form of the amino group, usually represented as NH3 + . The mechanism of the reaction of hydroxyl (-OH) with water molecules is mainly through the formation of hydrogen bonds. Hydroxyl is a hydrophilic group, and its interaction force with water molecules is similar to that of alcohol groups. The oxygen atom in the hydroxyl group can form hydrogen bonds with the hydrogen atoms in the water molecules. This interaction force is stronger than the general intermolecular force, but weaker than the chemical bond. The formation of hydrogen bonds gives hydroxyl groups good solubility and compatibility. Although both amino (-NH2) and hydroxyl (-OH) groups can catalyze the dissociation of water molecules, it can be seen from the comparison results that the bipolar membrane containing a hydroxyl MOF catalyst intermediate layer has a better catalytic effect. It not only increases the effective active area of ​​the water dissociation reaction, but also enhances the interfacial field strength, further promotes the polarization effect of water molecules, and accelerates the kinetic process of the water dissociation reaction.

[0051] In summary: the present invention utilizes anion exchange resin and cation exchange resin, adds a binder, uses hydroxyl MOF material as a water dissociation catalyst, and is produced by a tape casting method to obtain a high-performance and high-stability bipolar membrane containing a hydroxyl MOF catalyst intermediate layer. The raw material price of the preparation method of the present invention is cheap, the production process is simple, the prepared bipolar membrane has a stable structure and a long service life. The present invention utilizes hydroxyl MOF material as a water dissociation catalyst, and contains hydroxyl groups and metal groups at the same time. The catalytic effect of hydroxyl groups and the porous structure of the MOF material itself have strong adsorption properties and can effectively extend the specific surface area of ​​the catalyst. The metal group has hydration ability and plays a role as an active surface site in the ion exchange membrane matrix, which helps to enhance the transfer of protons from water molecules to fixed charge groups, accelerates water dissociation in the bipolar membrane, and thus promotes the bipolar membrane containing a hydroxyl MOF catalyst intermediate layer to have a faster hydrolysis rate. The present invention shows that in the research of bipolar membranes, the design of bipolar membrane materials and the selection of hydroxyl MOF water dissociation catalysts have broad development prospects for the development of new and excellent bipolar membranes.

[0052] The above description is only a detailed description of the preferred embodiments and principles of the present invention. For ordinary technicians in this field, according to the ideas provided by the present invention, there will be changes in the specific implementation methods, and these changes should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer, characterized in that: The following steps are involved: (S.1) Preparation of hydroxyl MOF water dissociation catalysts: Weighing hydrated metal chloride and dissolving it in N,N-dimethylformamide solution, adding 2-hydroxyterephthalic acid, stirring evenly and sealing it in a reaction kettle, cooling it naturally after the heating reaction is completed, taking the product and centrifuging, washing and drying it to obtain a hydroxyl MOF hydrolysis catalyst M-MOF-OH; (S.2) Preparation of bipolar membrane: Add anion exchange resin powder and cation exchange resin powder to the binder solution respectively, stir evenly, and obtain anion membrane casting solution and cation membrane casting solution respectively; fix the woven fabric on a clean glass plate and cast the anion membrane casting solution thereon and dry it, and obtain the anion exchange membrane layer after it is completely dried; An ethanol solution containing a hydroxyl MOF water dissociation catalyst M-MOF-OH is dripped onto the anion exchange membrane layer and dried to obtain an intermediate layer after complete drying; A cationic membrane casting solution is coated on the intermediate layer and dried, thereby forming a cation exchange membrane layer on the intermediate layer, and finally obtaining a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer.

2. The method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer according to claim 1, characterized in that: The metal ion contained in the hydrated metal chloride in step (S.1) is Al 3+ Mg 2+ Sn 2+ , any one or more combinations of transition metal ions.

3. The method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer according to claim 1, characterized in that: The molar ratio of the metal ion contained in the hydrated metal chloride to the 2-hydroxyterephthalic acid is 0.1-1:0.5-1.

4. The method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer according to claim 1, characterized in that: In step (S.1), the amount of N,N-dimethylformamide solution added is 30-60 mL.

5. The method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer according to claim 1, characterized in that: In step (S.1), the stirring reaction time is 30-100 min; the reaction temperature of the heating reaction is 120-180° C., and the reaction time of the heating reaction is 10-18 h.

6. The method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer according to claim 1, characterized in that: The cation exchange groups contained in the cation exchange resin powder in step (S.2) are any one or more combinations of sulfonic acid groups, carboxyl groups, phosphonic acid groups, phosphinic acid groups, arsenic acid groups and selenic acid groups; The anion exchange groups contained in the anion exchange resin powder are any one or more combinations of quaternary ammonium salts, primary amines, secondary amines, tertiary amines, and tertiary sulfonium groups; The binder contained in the binder solution is any one or more combinations of polyacrylonitrile, polyethylene, polyvinyl chloride, polyvinyl alcohol, fluororubber, styrene-butadiene rubber, cellulose derivatives, polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinylidene fluoride, polysulfone, polyetheretherketone, styrene-ethylene-butylene-styrene, and polyphenylene ether.

7. The method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer according to claim 1, characterized in that: The concentration of the binder solution in step (S.2) is 2-15%; The mass ratio of the anion and cation exchange resin powder contained in the anion and cation membrane casting solution to the binder contained in the binder solution is 0.2~1.5:1; The concentration of anion membrane casting solution and cationic membrane casting solution is 5~20%; The concentration of the ethanol solution containing the hydroxyl-based MOF water dissociation catalyst M-MOF-OH is 0.05~0.2g / L.

8. The method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer according to claim 1, characterized in that: The drying temperature in step (S.2) is 50-60°C.

9. The bipolar membrane containing a hydroxyl MOF catalyst intermediate layer prepared by the preparation method according to any one of claims 1 to 8, comprising an anion exchange membrane layer, an intermediate layer having a water dissociation catalytic effect and a cation exchange membrane layer in sequence, characterized in that: The intermediate layer includes a MOF catalyst containing hydroxyl groups.

10. Application of the method for preparing a bipolar membrane containing a hydroxyl MOF catalyst intermediate layer as claimed in any one of claims 1 to 8 in the fields of photo / electrochemical hydrolysis hydrogen production process, fuel cell, electrochemical ammonia synthesis process, and bipolar membrane electrodialysis.

Citation Information

Patent Citations

  • Electrolyte modulator, fabrication methods and applications of same

    CN110915055A

  • Ion conduction type metal-organic framework thin film chemical sensor and preparation method thereof

    CN111103094A

  • Fusiform MnFeNi-MOF-74 material growing on foamed nickel in situ as well as preparation method and application of fusiform MnFeNi-MOF-74 material

    CN112058309A

  • Metal organic framework crystal film for all-vanadium redox flow battery

    CN113903938A

  • MOF-loaded bipolar membrane and application thereof

    CN115245762A

Cited By

  • Preparation method of adhesive bipolar membrane

    CN119548999A

  • A method for preparing a bonded bipolar membrane

    CN119548999B

  • Interface modified composite membrane for producing hydrogen by electrolyzing water and preparation method of interface modified composite membrane

    CN120006349A

  • Bipolar membrane containing middle catalyst layer of MOF (Metal Organic Framework) as well as preparation method and application of bipolar membrane

    CN120082926A

  • Bipolar membrane as well as preparation method and application thereof

    CN122057378A